Bibliometric Analysis: Trends In Studies On Realistic Mathematics Education Learning to Enhance Mathematical Reasoning Abilities - Risantika Risantika; Effie Efrida Muchlis; Anny Sovia; Edi Susanto; Ringki Agustinsa (Universitas Wiralodra, 2025)
Mathematical reasoning is an important aspect of mathematics education that involves logical thinking, problem analysis, and drawing conclusions based on existing data. Realistic Mathematics Education (RME) connects mathematical concepts with real situations that train students' logical thinking so that reasoning skills tend to improve. Therefore, it is important to analyze the development of RME research on reasoning skills. This analysis presents a bibliometric analysis of the literature on RME-based learning to improve mathematical reasoning, using data from Google Scholar accessed through the Publish Or Perish software and analyzed with the help of VOSViewer software. Through keyword searches for